Synthesis, characterization, and polymerization of new hydroxyethyl methacrylate containing cyclobutane ring - Coskun, M; Demirelli, K; Ahmetzade, MA (Marcel Dekker Inc, 1997)
2-(3-Chloro-3-methylcyclobutyl)-2-hydroxyethyl methacrylate was prepared from the reaction of methacrylic acid with the oxirane compound obtained from the chlorhydrin formed in the cyclization of 1-chloro-2, 3-epoxy-5-methyl-5-hexene. This is a new methacrylate ester. Polymerization of this monomer was carried out in 1,4-dioxane solution at 60 degrees C using benzoyl peroxide as the initiator. Activation energy for the polymerization was found to be 7.33 kcal/mol from experiments done at three different temperature. Weight-average molecular weight of the polymer obtained at 60 degrees C was determined to be 67,572 by the GPC technique. The DSC curve showed a glass transition at 83 degrees C. infrared, proton, and carbon-13 nuclear magnetic resonance techniques were used in characterization of the monomer and its homopolymer. The TGA curve of the polymer was investigated by comparing it with that of poly(2-hydroxyethyl methacrylate).
Keywords: Poly(2-Hydroxyethyl Methacrylate); Functional Monomers; Acid